2000
DOI: 10.1103/physrevlett.85.4152
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Persistent Currents due to Confinement in Metallic Samples

Abstract: Confinement and surface roughness (SR) effects on the magnitude of the persistent current are analyzed for ballistic bidimensional metallic samples. Depending on the particular geometry, localized border states can show up at half-filling. These border states contribute coherently to the persistent current and its magnitude is enhanced with respect to their value in the absence of confinement. A linear scaling of the typical current I(typ) with the number of conduction channels M is obtained. This result is ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Much experimental work has been carried out on ensembles of rings/quantum dots 6,7 in a flux as well as on single metallic 8,9,10,11,12 or semiconductor quantum dots/rings 13,14,15,16 . The subject has a long theoretical history as well 17,18,19,20,21,22,23,24,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Much experimental work has been carried out on ensembles of rings/quantum dots 6,7 in a flux as well as on single metallic 8,9,10,11,12 or semiconductor quantum dots/rings 13,14,15,16 . The subject has a long theoretical history as well 17,18,19,20,21,22,23,24,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…11 In a recent work we have shown that by effect of confinement, large values of PC's can arise in the half filling regime for clean metallic cavities of different shapes. 12 In this paper we address the effect of bulk disorder in confined metallic systems threaded by a magnetic flux. We are mainly concerned with the interplay between confinement and disorder effects and in particular with the sensitivity of the persistent current to the strength of disorder w. Our main result is that even deep in the diffusive regime large values of persistent currents can still be obtained for a wide variety of sample shapes.…”
mentioning
confidence: 99%
“…12, with the additional inclusion of diagonal disorder. Once the profile of the sample is defined, the on-site energies are taken randomly distributed in the interval ͓Ϫw/2,w/2͔.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A treatment of Ref. 28, which models surface disorder by cutting off the boundary sites by confining potential and eventually proceeds with numerical evaluation of persistent currents, seems to describe a similar physical situation.…”
Section: Introductionmentioning
confidence: 99%